Formation of Creative Abilities in Children Through Play Activities - Islamova Shahlo Azam kizi (Uzbekistan Open Conference, 2025)
This article analyzes the role of play in the development of children's creative thinking. It examines the psychological and pedagogical foundations of this process, practical methods for fostering creativity through play-based activities, the influence of the play environment on the quality of education, and the integration of game-based technologies into the preschool education system. The findings indicate that play activities are among the most effective means of developing children's independent thinking skills and their ability to find creative, non-standard solutions.
Keywords: Creativity; play activities; developmental education; creative thinking; preschool education; pedagogy; game-based technologies